2022
DOI: 10.2196/24582
|View full text |Cite
|
Sign up to set email alerts
|

Scale-up of Digital Innovations in Health Care: Expert Commentary on Enablers and Barriers

Abstract: Health care delivery is undergoing a rapid change from traditional processes toward the use of digital health interventions and personalized medicine. This movement has been accelerated by the COVID-19 crisis as a response to the need to guarantee access to health care services while reducing the risk of contagion. Digital health scale-up is now also vital to achieve population-wide impact: it will only accomplish sustainable effects if and when deployed into regular health care delivery services. The question… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 45 publications
(45 reference statements)
2
25
0
Order By: Relevance
“…Participants re ected on a wide range of variables in uencing uptake and engagement. Consistent with previous research, factors such as user-friendliness, personalization, gami cation and social in uences were suggested as facilitators to engagement (54-57), while lack of digital literacy, poor clinical work ow integration, and technical issues were highlighted as barriers (30,33,55,58). A noteworthy difference to previous studies (mostly conducted with Western populations) is the in uence that government endorsement has on a users' decision whether to start using a given digital health intervention or not.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Participants re ected on a wide range of variables in uencing uptake and engagement. Consistent with previous research, factors such as user-friendliness, personalization, gami cation and social in uences were suggested as facilitators to engagement (54-57), while lack of digital literacy, poor clinical work ow integration, and technical issues were highlighted as barriers (30,33,55,58). A noteworthy difference to previous studies (mostly conducted with Western populations) is the in uence that government endorsement has on a users' decision whether to start using a given digital health intervention or not.…”
Section: Discussionsupporting
confidence: 82%
“…A key challenge for any digital health intervention lies in how to motivate users to start using the app, website, and/or wearable device and adhere to it long enough (27,30). Participants re ected on a wide range of variables in uencing uptake and engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Panel reviews including a broad spectrum of stakeholders identified several dozens of facilitators and barriers for upscaling and implementing digital health solutions in healthcare [63]. More specifically, Connolly and coworkers [46] have provided suggestions for factors of success of implementing digital tools in routine mental healthcare, including but not limited to providing clinician and support staff training, integrating digital solutions into clinical workflows, and safety planning and defining borders of clinician responsibilities given the possible 24/7 use of digital technologies by patients.…”
Section: Recommendations For Mental Healthcare Professionalsmentioning
confidence: 99%
“…A recent review identified 247 distinct initiatives, ranging from AI and big data to diagnose and screen for COVID-19 infection, to provision of telehealth for healthcare access [47]. A common issue with data-driven solutions is scalability and integration into healthcare systems [48].…”
Section: Comparison With Existing Literaturementioning
confidence: 99%